Epidemiology of injuries in National Collegiate Athletic Association women's swimming and diving: 2014-2015 through 2018-2019 - Chandran, A.; Morris, S. N.; D'Alonzo, B. A.; Boltz, A. J.; Robison, H. J.; Collins, C. L. (Journal of Athletic Training, 2021)
Context: The number of women's swimming and diving teams sponsored by the National Collegiate Athletic Association has increased over the last 5 years. Background: Routine examinations of women's swimming and diving injuries are important for identifying emerging temporal patterns. Methods: Exposure and injury data collected in the National Collegiate Athletic Association Injury Surveillance Program during the 2014-2015 through 2018-2019 athletic seasons were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics, and injury rate ratios were used to examine differences in injury rates. Results: The overall injury rate was 1.78 per 1000 athlete-exposures in swimmers and 2.49 per 1000 AEs in divers. Shoulder (33.0%) injuries accounted for the largest proportion of all swimming injuries; most injuries were classified as overuse (51.3%). Head or face (29.4%) and trunk (20.2%) injuries accounted for the largest proportions of all diving injuries. Summary: Findings indicated that shoulder and trunk injuries, as well as injuries resulting from overuse mechanisms, warrant further attention in swimming. Given the low in the National Collegiate Athletic Association Injury Surveillance Program observed across the study period, the need for greater participation in sports injury surveillance is also apparent.